Effectiveness of STEM (Science, Technology, Engineering, Mathematics) Approach Towards Mathematics Learning Achievement on Point, Line and Field Material in Three Dimensions - Imam Bakhtiar; Lenny Kurniati; Akhmad Nayazik (Hipotenusa : Journal of Mathematical Society, 2020)
This study aims to determine the effectiveness of the STEM approach to mathematics learning achievement in class XI Machining Engineering Expertise Competency at SMK NU Maarif Kudus. The research objects are class XI TP 4 (control class) and class XI TP 5 (experimental class) in the 2019/2020 school year. This type of research is quantitative research with posttest only control design. The sample selection was based on observations and recommendations from the mathematics teacher and obtained class XI TP 5 as an experimental class was treated with the learning process with the STEM approach and class XI TP 4 as a control class. The t test results (independent sample t-test) showed that the Sig. (2-tailed) 0.036 0.05. This means that from the hypothesis that was built, Ho was rejected and Ha was accepted. From the results of tests conducted it can be said that there are significant mean differences between classes with the STEM approach compared with the scientific approach. Besides the STEM approach is more effective in giving an impact on student achievement.